Corporate image. - Lee, Meng Wei. (2008)
Corporate image has generated a tremendous amount of interest in the recent years. This is due to companies realizing the importance and benefits of a good image. The motivation of our research comes from this increased emphasis on corporate image. Our research was conducted to assess the importance of corporate image, analyze the factors that affect corporate image, and recommend ways that a company can take to enhance its corporate image.